2023
DOI: 10.1002/ajh.26837
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal fentanyl and discharge from the emergency department among children with sickle cell disease and vaso‐occlusive pain: A multicenter pediatric emergency medicine perspective

Abstract: Children with sickle cell disease (SCD) commonly experience vaso‐occlusive pain episodes (VOE) due to sickling of erythrocytes, which often requires care in the emergency department. Our objective was to assess the use and impact of intranasal fentanyl for the treatment of children with SCD‐VOE on discharge from the emergency department in a multicenter study. We conducted a cross‐sectional study at 20 academic pediatric emergency departments in the United States and Canada. We used logistic regression to test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Intranasal fentanyl should be used as a bridge to administration of intravenous opioids due to its ease and rapidity of administration and has been associated with increased likelihood of discharge in children and young adults with SCD. 14 Patients should be reassessed every 30-60 minutes for pain relief and side effects. If pain persists, an opioid should be readministered every 30-60 minutes until pain is under control.…”
Section: Initial Managementmentioning
confidence: 99%
“…Intranasal fentanyl should be used as a bridge to administration of intravenous opioids due to its ease and rapidity of administration and has been associated with increased likelihood of discharge in children and young adults with SCD. 14 Patients should be reassessed every 30-60 minutes for pain relief and side effects. If pain persists, an opioid should be readministered every 30-60 minutes until pain is under control.…”
Section: Initial Managementmentioning
confidence: 99%
“…Regarding sedative, antidepressant or antianxiety drugs, ketamine and dexmedetomidine are the most studied (Table 2). There is evidence in the medical literature of the high effectiveness, efficiency, and ease of intranasal use of these drugs [32,43,46]. Interesting findings are presented in the review by Lemus et al (2022) where, based on a series of case reports, dexmedetomidine was shown to be highly effective in palliative and hospice care [59].…”
Section: Sedative Antidepressant and Antianxiety Drugsmentioning
confidence: 99%
“…Vaso-occlusive episodes (VOEs) in patients with sickle cell disease (SCD) often require strong opiate analgesia and may necessitate hospital admission. This observational study determined the association of intranasal fentanyl with rates of hospital admission in children and young people presenting to ED with VOE 3…”
Section: Intranasal Fentanyl and Discharge From The Emergency Departm...mentioning
confidence: 99%